Dose-response effects of dietary pequi oil on fermentation characteristics and microbial population using a rumen simulation technique (Rusitec). (December 2017) - Duarte, Andrea Camacho; Durmic, Zoey; Vercoe, Philip E.; Chaves, Alexandre V.
Abstract: The effect of increasing the concentration of commercial pequi ( Caryocar brasiliense ) oil on fermentation characteristics and abundance of methanogens and fibrolityc bacteria was evaluated using the rumen simulation technique (Rusitec). In vitro incubation was performed over 15 days using a basal diet consisting of ryegrass, maize silage and concentrate in equal proportions. Treatments consisted of control diet (no pequi oil inclusion, 0 g/kg DM), pequi dose 1 (45 g/kg DM), and pequi dose 2 (91 g/kg DM). After a 7 day adaptation period, samples for fermentation parameters (total gas, methane, and VFA production) were taken on a daily basis. Quantitative real time PCR (q-PCR) was used to evaluate the abundance of the main rumen cellulolytic bacteria, as well as abundance of methanogens. Supplementation with pequi oil did not reduce overall methane production ( P  = 0.97), however a tendency ( P  = 0.06) to decrease proportion of methane in overall microbial gas was observed. Increasing addition of pequi oil was associated with a linear decrease ( P  < 0.01) in dry matter disappearance of maize silage. The abundance of total methanogens was unchanged by the addition of pequi oil, but numbers of those belonging to Methanomassiliicoccaceae decreased in liquid-associated microbes (LAM) samples ( P < 0.01) and solid-associated microbes (SAM) samples ( P  = 0.09) respectively, while Methanobrevibacter spp. increased ( P  < 0.01) only in SAM samples. Fibrobacter succinogenes decreased ( P  < 0.01) in both LAM and SAM samples when substrates were supplemented with pequi oil. In conclusion, pequi oil was ineffective in mitigating methane emissions and had some adverse effects on digestibility and selected fibrolytic bacteria. Highlights: Effect of an exotic oil from Cerrado in Brazil on ruminal microbial fermentation. Pequi oil decreased CH4 (%). Increasing dose of pequi oil altered microbial populations.